PENERAPAN MODEL TALKING STICK PADA MATERI JENIS-JENIS PEKERJAAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 7 PIDIE - Nufiar (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
The research was about how was Talking Stick Model applied in the topic: Types of Job and whether talking stick model could improve students’ learning achievement at fourth grade students of MIN 7 Pidie. The research aimed to find out how Talking Stick Model applied in the topic: Types of Job to the fourth grade students of MIN 7 Pidie and to know if Talking stick could increase students’ achievements. The type of the research conducted was Classroom Action Research . the subjects were the fourth grade students year 2019/2020 which totally 24 students. The technique of collecting data employed observation, interview , documentation and test. The findings showed; the students got average and classical achievements respectively: in cycle I 59.37 and 33.33%; and cycle II 88,08 and 100%. So, Talking Stick Model can improve students’ learning achievements in type of Job topic.